Analysis the Strength of Mild Steel Material on a Handcycle Bike Frame - Andika Wisnujati; Rela Adi Himarosa (Logic : Jurnal Rancang Bangun dan Teknologi, 2021)
The frame is one of the most important parts in a series of constituents of a bicycle. The materials for making bicycle frames usually use tight and strong materials such as stainless steel, carbon and titanium. Mild steel is steel with low carbon, which is about 0.05-0.30%. After conducting a tensile test on the mild steel material used on the handcycle bicycle frame, the highest stress results were 1,093.87 N/mm² and the highest strain was 0.167%. For the results of stress analysis contained in the autodesk inverter, the von mesess results are obtained for men weighing 70 kg von mesess maximum 1400 mpa and women weighing 60 kg 1200 mpa. The maximum displacement generated for men weighing 70 kg 96.63 mm and women weighing 60 kg 82.83 mm. For the safety factor obtained based on the safety number from Dobrovolsky for static loads, the safety number is 1.25-2; dynamic load 2-3 shock load 3-5 while the safety rate that occurs in the load is 0.15 for men weighing 70 kg and 0.16 for women weighing 60 kg. So the handcycle bikes that we made are safe to ride because the results obtained are still below existing standards